2003
DOI: 10.1007/s11745-003-1065-1
|View full text |Cite
|
Sign up to set email alerts
|

The potential role for arachidonic and docosahexaenoic acids in protection against some central nervous system injuries in preterm infants

Abstract: The risk of central nervous, visual, and auditory damage increases from 2/1000 live births in the normal birthweight to > 200/1000 as birthweight falls below 1500 g. Such babies are most likely to be born preterm. Advances in infant care have led to increasing numbers of very-low-birthweight, preterm infants surviving to school age with moderate to severe brain damage. Steroids are one of the current treatments, but they cause significant, long-term problems. The evidence reported here suggests an additional a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
95
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(99 citation statements)
references
References 80 publications
2
95
0
2
Order By: Relevance
“…Considering the anti-inflammatory effect of DHA, and of its downstream metabolite eicosanoids, 51,52 authors have argued that DHA deficits in preterm infants may have considerable, underestimated adverse effects during the neonatal period. 9,10,53,54 In light of the strong association between elevated inflammation and both shortand long-term morbidities in extreme preterm infants, 48,55 we postulate that a DHA supplementation or a decrease in the omega-6/omega-3 reduces the occurrence of these major adverse neonatal outcomes, including BPD. Of note, when specifically examining studies in which omega-6 lipids were coadministered with DHA, we detected no additional benefit on BPD compared with studies using DHA alone (Fig 2B), indicating a selective role of DHA or the ratio omega-6/omega-3.…”
Section: Figurementioning
confidence: 99%
“…Considering the anti-inflammatory effect of DHA, and of its downstream metabolite eicosanoids, 51,52 authors have argued that DHA deficits in preterm infants may have considerable, underestimated adverse effects during the neonatal period. 9,10,53,54 In light of the strong association between elevated inflammation and both shortand long-term morbidities in extreme preterm infants, 48,55 we postulate that a DHA supplementation or a decrease in the omega-6/omega-3 reduces the occurrence of these major adverse neonatal outcomes, including BPD. Of note, when specifically examining studies in which omega-6 lipids were coadministered with DHA, we detected no additional benefit on BPD compared with studies using DHA alone (Fig 2B), indicating a selective role of DHA or the ratio omega-6/omega-3.…”
Section: Figurementioning
confidence: 99%
“…RXR is also able to bind FAs, and docosahexaenoic acid (DHA) has been shown to activate it (de Urquiza et al, 2000;Crawford et al, 2003). DHA deficiency in rat and humans results in abnormalities similar to those observed in RXR knock-out mice.…”
Section: Insidementioning
confidence: 99%
“…Docosahexaenoic acid and AA enhance growth in term and preterm infants (Clandinin et al, 1980, ) and have been shown to affect visual acuity and maturation of the visual cortex Birch et al, 2002). Docosahexaenoic acid and AA also affect cell signaling, maintain optimal states of fluidity and enhance neurovascular membrane integrity (Hardy and Kleinman, 1994;Jorgensen et al, 1996;Giovanni et al, 1998;Larque et al, 2002;Crawford et al, 2003;Uauy et al, 2003) as well as augment cognitive development (Agostoni et al, 1995;Birch et al, 2000,). Long-chain polyunsaturated fatty acids (LCPUFAs) may therefore play a very important role in growth and development in later childhood, yet intake data by preschool children are sparse, especially in developing countries.…”
Section: Introductionmentioning
confidence: 99%